RELIGIOUS LANGUAGE: Neither True nor False, but Meaningful - P, Radharani (Journal of Dharma, 2008)
The knowledge of knowing has attracted the attention of philosophers of all times. Knowledge begins with the acquisition of information and, hence, it is primary in philosophical, material, and other aspects of life. Intellectuals of the East as well as the West were very much drawn towards the interrelation of thoughts, words, sentences, and their meanings. It is through the medium of language that the thoughts and feelings can be expressed and, thus, human beings, unlike animals, with their special ability to express their thoughts and feelings through language, stands unique. Language is an abstract system employed primarily for communication and in the act of knowing, language occupies an important position.